Comprehensive Teleoptometry Exams in Canada: A Proposed Clinical Framework - Blais, Nicolas; Warren, Adrianna; Woo, Stan; Hanssens, Jean-Marie (Canadian Journal of Optometry, 2024)
Purpose: Many high-income countries like Canada are faced with unmet needs regarding the availability of access to eye care, especially in rural, remote, or northern areas. Teleoptometry has the potential to improve access to primary eye care and help prevent, detect, diagnose and treat uncorrected refractive error and sight-threatening eye diseases. Given the rapid adoption of technology for virtual care during the COVID pandemic, the existing teleoptometry guidelines in Canada are limited in scope and may lead to uncertainty for optometrists practicing remote care. The purpose of this paper is to build a scaffold that highlights the similarities and differences between an in-person comprehensive eye examination and one that is delivered through comprehensive teleoptometry in Canada. This proposed clinical framework draws from both the existing published literature and the clinical experience of the authors. This paper discusses issues for teleoptometry including patient consent, efficiency, delegation, training and the patient pathway including referral protocols when indicated. Results: Comprehensive teleoptometry eye exams are very similar to in-person eye exams, but they depend more on the assistance of an in-person technician/optometric assistant. The exams include delegated tests performed by an optometric assistant and tests controlled remotely by the optometrist like refraction. However, other tests that require clinical judgment to execute or interpret should be performed by the optometric assistant under the direct supervision of the remote optometrist using live video. The remote optometristbe able to repeat any test during videoconferencing. Conclusion: Teleoptometry is a tool optometrists can use to reach patients that struggle to access an in-person eye exam. This evidence-informed, draft framework provides a point of reference for discussion by the Federation of Optometric Regulatory Authorities of Canada and the provincial regulatory authorities to protect the public and increase access through the delivery of remote primary eye care in Canada.